Vitamin and trace elements imbalance are very common in adult patients with newly diagnosed Celiac disease - Kailibinuer Nuermaimaiti; Ting Li; Na Li; Tian Shi; Weidong Liu; Paziliya Abulaiti; Kamiran Abulaihaiti; Feng Gao (Scientific Reports)
Abstract Patients with celiac disease are at risk of micronutrient deficiencies due to long-term inflammation of the small intestine. Therefore, our aim was to investigate the correlation between CeD and micronutrients. A cross-sectional study enrolled a total of 59 newly diagnosed celiac patients and 59 controls. Levels of 17 vitamins and 10 trace elements were measured. Symptoms, serum IgA anti-TG2 (tTG-IgA), BMI, albumin, hemoglobin, and Marsh classification were recorded. The levels of micronutrients were compared between cases and controls, and correlations between micronutrients and other factors were analyzed. Celiac patients had lower levels of BMI, albumin, hemoglobin, vitamins A, E, K2 (MK-7, MK-4), B6, and B7, as well as zinc, and higher levels of vitamin B3 and chromium than controls (p < 0.05). The deficiency rates of vitamins A, E, and K2 (MK-7) and the excess rate of vitamin B3 were significantly higher than in controls (p < 0.05). Vitamin C, iron and calcium levels were negatively correlated with Marsh classification, while vitamin D and E levels were negatively correlated with serum tTG-IgA levels (p < 0.05). The vitamin A level in classical patients was lower than in non-classical patients (p < 0.01). In conclusion, micronutrient imbalance is very common in celiac patients, including both deficiencies and excesses. Therefore, it is necessary to assess micronutrient levels in newly diagnosed celiac patients.